Algoritma C4.5 untuk Memprediksi Loyalitas Konsumen Pada PT. HIBA UTAMA - Apriana, Veti; Fauziah , Sifa; Yani , Ahmad; Supriyatna , Adi; Christian , Ade; Sumarna , Sumarna; Fahmi , Muhammad (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
HIBA UTAMA is a company engaged in the transportation sector or often also called PO (Otobus Company) a company that is managed and operated to provide bus rental services and provide convenience to its consumers. The existence of the company has a significant role in providing transportation for consumers to travel and provide comfort and safety on the way. Competition that occurs makes companies vying to provide the best service to consumers. On the other hand consumers are increasingly difficult to understand. Satisfied consumers are not necessarily going to rent again and loyal consumers are not necessarily satisfied with the services provided. Most companies measure consumer satisfaction, but only a few assess customer loyalty and the results of PT. HIBA UTAMA helps increase consumer loyalty. Researchers apply the C4.5 algorithm to predict consumer loyalty at PT. HIBA UTAMA. The variables used are tenant period, rental scale, compliance, tenant loyalty, based on the accuracy results reaching 81%, which shows the C4.5 algorithm is suitable for predicting company customer loyalty.